Building Character Through the Qur’an and Hadith: Hadith’s Review the Wisdom Behind the Invisibility of God, Heaven and Hell - Purwantoro (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2024)
Character formation in Islam plays a very important role in shaping the attitudes and morals of Muslims to be in accordance with religious teachings. This study aims to analyze how the concept of the invisibility of God and the afterlife taught in the hadith of the Prophet Muhammad saw can contribute to the development of good character. Using a qualitative approach and library research method, this study reveals the relationship between belief in the invisibility of God and the afterlife with the formation of a Muslim’s character. The belief that God is invisible teaches Muslims to be humble, patient, and obedient to His commands, while belief in the afterlife encourages them to do good, maintain morals, and focus on the afterlife. The hadiths of the Prophet Muhammad saw provide clear instructions on how Muslims can live a life that focuses on happiness in this world and the hereafter. This study shows that belief in the invisibility of God and the afterlife plays a major role in shaping better character and providing encouragement to do good in everyday life. The author also suggests that Muslims deepen their understanding of the hadiths and apply them in everyday life to improve morals and achieve happiness in the hereafter.